Design of a single phase switch mode AC-DC Converter - Surjo, Md. Rafiqur Rahman; Amin, Md. Afsarul (BRAC University, 2012)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Electrical and Electronic Engineering, 2011.